Comparison of Da Vinci XI and Da Vinci SI Surgical Systems in Robot-Assisted Radical Prostatectomy - A. O. Papoyan; M. F. Urmantsev; V. N. Pavlov (Креативная хирургия и онкология, 2024)
Introduction. Robot-assisted radical prostatectomy is considered to be the “gold standard” for the radical treatment of prostate cancer, achieving excellent oncological outcomes with a low incidence of complications.Aim. To analyze and compare the efficiency of Da Vinci Xi and Da Vinci Si surgical systems applied in performing robot-assisted radical prostatectomy. Materials and methods. 165 patients were divided into two groups: Xi-group (n = 77) and Si-group (n = 88). The perioperative characteristics and oncological outcomes were analyzed and compared.Results. The demographic, clinical, and oncological characteristics of the two patient groups appeared similar and comparable. Interventions involving the preservation of the neurovascular bundle, the pelvic fascia, and the puboprostatic ligament were performed using Xi system significantly more often. The surgery duration was significantly shorter in the Xi-group. The postoperative recovery time and the incidence of postoperative complications appeared to be identical across both groups. No differences were revealed in the rates of positive surgical margins or biochemical recurrence.Discussion. Reasons behind the reduced operative time were considered as follows: first, the docking of the Xi system is more user-friendly, resulting in decreased docking time; second, the operational efficiency of the Xi system had been enhanced, thereby leading to reduced workflow times; third, a number of collisions between robotic arms was significantly lower during the procedure, which accelerates the surgical process.Conclusion. A robot-assisted radical prostatectomy performed by an experienced professional, using the Da Vinci Xi or Da Vinci Si surgical systems, appears to be safe and feasible without an increased risk of serious complications. However, the Xi system ensures better perioperative outcomes with comparable oncological results.